A light in the dark: a mid-Cretaceous bioluminescent firefly with specialized antennal sensory organs - Cai, Chenyang; Tihelka, Erik; Ballantyne, Lesley; Li, Yan-Da; Huang, Diying; Engel, Michael S; Kundrata, Robin (Proceedings. Biological sciences, 2024)
The beetle superfamily Elateroidea comprises the most biodiverse bioluminescent insects among terrestrial light-producing animals. Recent exceptional fossils from the Mesozoic era and phylogenomic studies have provided valuable insights into the origin and evolution of bioluminescence in elateroids. However, due to the fragmentary nature of the fossil record, the early evolution of bioluminescence in fireflies (Lampyridae), one of the most charismatic lineages of insects, remains elusive. Here, we report the discovery of the second Mesozoic bioluminescent firefly, Flammarionella hehaikuni Cai, Ballantyne & Kundrata gen. et sp. nov., from the Albian/Cenomanian of northern Myanmar (ca 99 Ma). Based on the available set of diagnostic characters, we interpret the specimen as a female of stem-group Luciolinae. The fossil possesses deeply impressed oval pits on the apices of antennomeres 3-11, representing specialized sensory organs likely involved in olfaction. The light organ near the abdominal apex of Flammarionella resembles that found in extant light-producing lucioline fireflies. The growing fossil record of lampyrids provides direct evidence that the stunning light displays of fireflies were already established by the late Mesozoic.
Keywords: Luminescence; diversity; Phylogeny; světluškovití; zkameněliny; Female; Biological Evolution; zvířata; Myanmar; ženské pohlaví; fylogeneze; biologická evoluce; bioluminescence; Lampyridae; Arthropod Antennae; Fireflies; Mesozoic; Animals; tykadla členovců; luminiscence; Fossils